2020
DOI: 10.1038/s41385-019-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

NK cell recruitment limits tissue damage during an enteric helminth infection

Abstract: Parasitic helminths cause significant damage as they migrate through host tissues to complete their life cycle. While chronic helminth infections are characterized by a well-described Type 2 immune response, the early, tissue-invasive stages are not well understood. Here we investigate the immune pathways activated during the early stages of Heligmosomoides polygyrus bakeri (Hpb), a natural parasitic roundworm of mice. In contrast to the Type 2 immune response present at later stages of infection, a robust Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…1 ). A recent study also reported increased IFNγ gene expression in the early stage of Hp infection, which is consistent with our results [ 3 ]. It has been previously demonstrated that IFNγ is a key factor in the regulation of ILC2 [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…1 ). A recent study also reported increased IFNγ gene expression in the early stage of Hp infection, which is consistent with our results [ 3 ]. It has been previously demonstrated that IFNγ is a key factor in the regulation of ILC2 [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
“…As mentioned above, Th2 differentiation relies on ILC2s, and ILC2s require CD4+ T cells to survive. Cells that produce IFNγ, which is believed to be important for switching the role from ILC2 to CD4, are still unidentified, but NK cells accumulate before ILC2 in the early stages of infection, and IFNγ is involved [ 3 ]. We could not analyze which cell population produces IFNγ; therefore, further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…At the infection site, we observed a significant decrease in small intestinal length among Hpb HA107 à GF ( Figure 4E). Furthermore, these mice displayed a uniform inability to resolve tissue granulomas ( Figure 4F) -formations that typically arise during the tissue invasive stage of the parasite and normally resolve within 7-10 days post-infection 8,15 . Indeed, at 14 days post-infection, all Hpb HA107 à GF subjects exhibited persistent granulomas that were not present in any other groups.…”
Section: Germ-free Hpb Infection Results In Increased Th2 Immunity Anmentioning
confidence: 99%
“…Based on our results, we speculate that persistent granulomas result from a dysregulated tissue repair process facilitated by an excessive Th2 response. We and others have recently described an early type 1 immune response, characterized by IFNg-producing natural killer cells, in proximity to the Hpb granuloma that promotes disease tolerance and tissue regeneration during infection 15,23 . Although it remains to be determined whether the microbiota is required for IFNg induction in this context, this may be one mechanism by which the host exploits the microbiota to counter the type 2 immune response and promote granuloma resolution.…”
Section: Discussionmentioning
confidence: 99%
“…During an infection trial with Cooperia oncophora in calves, NK cell proliferation increased (along with proliferation of T and B cells) after in vitro re-stimulation of mononuclear cells from mesenteric lymph nodes (68). More recent work on Heligmosomoides polygyrus bakeri, a natural parasitic roundworm of mice, has shown that recruitment of cytotoxic NK cells to the intestine early in infection increases host tolerance by mediating vascular integrity and endothelial cell survival (69). Very little published information regarding the role of NK cells during fasciolosis is available.…”
Section: Natural Killer Cell Activity Is Reducedmentioning
confidence: 99%